The Role of the United Nations in Environmental Sustainability and Sustainable Development - Ahmed, Siran Taha (Journal of Legal and Political Studies, 2018)
"Sustainable Development or Sustainability is a development that meets the needs of the present and uses natural resources in a way that will protect them for future generations. In Reality, development will not achieve its objectives without good environmental policies. Regarding, Human Development, it is a basic element, working with all other types of development, whether political, social or economic. Since development is a human right, the strong interdependence between human security and development can be achieved through the eradication of poverty, the promotion of democracy, the fight against famines, crises and conflicts, the emphasis on women's effectiveness, the promotion of culture and the defense of human rights and the improvement of access to social services, Health care, education, the promotion of gender equality and the follow of good governance approach. The United Nations and its organs play a fundamental role in the adoption of many international conferences, summits and reports in support and promotion of Sustainable Development. However, Human development has become a priority for the international community, since lack of development poses a threat to international peace and security. Therefore, it is necessary the cooperation at the national and international levels must be strengthened in the pursuit of sustainable development. At the same time, States and the international community also strive to move towards sustainable development by building capacity and providing technology support to developing countries, and also requires governments and decision-makers in the countries to adopt a sustainable approach in governance and to making laws and regulations which respond all needs to achieve Sustainable development."
Keywords: natural resources; environmental policies; human rights; Gender equality